Rumination and psychological resilience in Chinese civil aviation flight students: the chain mediating role of proactive coping and generalized anxiety disorder - Liao, Mingyu; Wang, Haozhe; Liu, Zongyu; Hu, Enliang (Frontiers in Psychology, 2025)
BackgroundAs the focus of aviation safety shifts from technology to human factors, the central role of psychological resilience in flight safety has become increasingly prominent. However, the internal mechanism of how rumination affects psychological resilience, particularly the chain mediating effect of proactive coping and generalized anxiety, has not been thoroughly explored in high-stress populations.MethodsEmploying a cross-sectional design, 1,235 flight students from the Civil Aviation Flight University of China were surveyed using the Ruminative Response Scale (RRS), Connor-Davidson Resilience Scale (CD-RISC), Simplified Coping Style Questionnaire (SCSQ), and Generalized Anxiety Disorder Scale (GAD-7) to gather data. Structural equation modeling (SEM) and the Bootstrap method were used to test the chain mediating effect.ResultsRumination exhibited a significant negative correlation with psychological resilience (r = −0.365, p < 0.01) and proactive coping (r = −0.285, p < 0.01), and a positive correlation with generalized anxiety (r = 0.337, p < 0.01). Psychological resilience showed a positive correlation with proactive coping (r = 0.727, p < 0.01) and a negative correlation with generalized anxiety (r = −0.270, p < 0.01). Mediation effect analysis revealed that proactive coping and generalized anxiety each played a partial mediating role between rumination and psychological resilience. The mediating effect comprised three paths: “rumination → proactive coping → psychological resilience,” “rumination → generalized anxiety → psychological resilience,” and “rumination → proactive coping → generalized anxiety → psychological resilience,” with effect sizes of 91.22, 7.80, and 0.98%, respectively.ConclusionRumination in civil aviation flight students not only directly impairs psychological resilience but also indirectly influences it through the chain mechanism of inhibiting proactive coping and intensifying generalized anxiety. Consequently, it is recommended that civil aviation psychological training focus on cognitive-behavioral interventions to interrupt the activation of rumination, foster adaptive coping strategies, and construct a psychological resilience development model tailored to the specific demands of the aviation profession.